Towards a means of consistently comparing airline business models with an application to the `low cost' airline sector - Mason, Keith J.; Morrison, William G. (Elsevier, 2008)
Meaningful definitions of and distinctions between airline business models are not easily formulated, particularly when one considers the extremely dynamic nature of the industry. The paper outlines a product and organizational architecture (POA) approach to classifying and relating key elements of airline business models. Using indices to create benchmark metrics, the POA model is then used to examine and compare six European airlines. The analysis shows that there are important differences in the business models of airlines that are all commonly referred to as ‘low cost carriers’. The paper demonstrates how differences in the business models adopted by the different airlines contribute to their relative profitability.
Keywords: Low cost carrier; Product and organizational architecture; Airline business models